A Review of Current Metaverse Applications as a Tool for Reshaping Human Behaviour in Health Communication - Hafizul Fahri Hanafi (Tanjung Malim, 2024)
A Review of Current Metaverse Applications as a Tool for Reshaping Human Behaviour in Health Communication by Hafizul Fahri Hanafi